Предмет: Алгебра,
автор: irisov2903
(X-1)(X-4)=3X
Решите как надо, и понятно
(X-2)(X+8)=6X
Ответы
Автор ответа:
1
1. х²-4х-х+4-3х=0
х²-8х+4=0
Д=64-4*1*4=64-16=48
х1,2= 4±v48 / 2
х1= 4+v48 / 2 = 4+2v12 / 2 = 2(2+v12) / 2 = 2+v12
х2= 4-v48 / 2 = 2-v12
2. х²+8х-2х-16-6х=0
х²-16=0
х²=16
х1,2= ±v16
x1=4, x2= -4
х²-8х+4=0
Д=64-4*1*4=64-16=48
х1,2= 4±v48 / 2
х1= 4+v48 / 2 = 4+2v12 / 2 = 2(2+v12) / 2 = 2+v12
х2= 4-v48 / 2 = 2-v12
2. х²+8х-2х-16-6х=0
х²-16=0
х²=16
х1,2= ±v16
x1=4, x2= -4
Похожие вопросы
Предмет: Математика,
автор: nyaroslavskaya0
Предмет: Русский язык,
автор: Biiik
Предмет: Информатика,
автор: auntcass
Предмет: Математика,
автор: олеся282
Предмет: История,
автор: karina98karina